KONSEP PENDIDIKAN BERBASIS FITRAH PADA KOMUNITAS SCHOLE FITRAH DI BOJONGSOANG DAN IMPLIKASINYA TERHADAP PROFESIONALISME GURU PAI - Tetin, - (2022)
Research about Fitrah Based Education concept at Schole Fitrah Community in Bojongsoang and its impact on Islamic education teachers professionalism has a short amount of information so this research purpose is to study and collect more information about it. Qualitative method approach with Cresswell study case design has chosen with interview, observation, and documentation study process to get most of the information with an additional analysis step like data display, data reduction, and data verification. The result is education based on fitrah concepts are starting with parents' concern about the present inadequate education system then, followed up by the intellectual education expert to initiate the true education system based on eight of the human fitrah. The eight fitrah classifications are faith, physical, learning and reasoning, sexuality and love, aesthetics and speech, talent and leadership, development, then individuality and sociality. Lastly, this research shows that Islamic education teachers have to ignite, rise and guide their students growth based on the eight fitrah dimensions refers to fitrah base education concept to expand Islamic education teachers professionalism. Key Word: Human Fitrah, Education based on Fitrah, Islamic Education teacher professionalism